The Cinematic Eighteenth Century - Swaminathan, Srividhya, author.
1 online resource (x, 196 pages)
Keywords: "This collection explores how film and television depict the complex and diverse milieu of the eighteenth century as a literary, historical, and cultural space. Topics range from adaptations of Austen's Sense and Sensibility and Defoe's Robinson Crusoe (The Martian) to historical fiction on the subjects of slavery (Belle), piracy (Crossbones and Black Sails), monarchy (The Madness of King George and The Libertine), print culture (Blackaddifer and National Treasure), and the role of women (Marie Antoinette, The Duchess, and Outlandifer). This interdisciplinary collection draws from film theory and literary theory to discuss how film and television allows for critical re-visioning as well as revising of the cultural concepts in literary and extra-literary writing about the historical period."--Provided by publisher.